2007
DOI: 10.1111/j.1471-0528.2007.01572.x
|View full text |Cite
|
Sign up to set email alerts
|

Manual versus electric vacuum aspiration for first‐trimester abortion: a systematic review

Abstract: Background As an alternative to electric vacuum aspirations (EVA), there is an increasing interest in using manual vacuum aspiration (MVA).Objective To compare the safety, efficacy and acceptability of MVA with those of EVA for first-trimester abortion.Search strategy We searched MEDLINE, EMBASE, Cochrane Library and Chinese Biomedical Database in all language, together with reference lists of retrieved papers.Selection criteria Randomised controlled trials comparing MVA with EVA for first-trimester abortion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 22 publications
(78 reference statements)
8
61
0
2
Order By: Relevance
“…The operating time for MVA was significantly longer than EVA in our study. Similar observations were made by Wen et al 7 in BJOG 2007 in the meta analysis of 10 studies with a gestational age of less than 50 days and by Nasira et al 8 in 2011 (Operating time (min) mean ± SD 10.71 ± 2.770 for MVA and 9.59 ± 2.880 for EVA, P<0.01).…”
Section: Discussionsupporting
confidence: 84%
“…The operating time for MVA was significantly longer than EVA in our study. Similar observations were made by Wen et al 7 in BJOG 2007 in the meta analysis of 10 studies with a gestational age of less than 50 days and by Nasira et al 8 in 2011 (Operating time (min) mean ± SD 10.71 ± 2.770 for MVA and 9.59 ± 2.880 for EVA, P<0.01).…”
Section: Discussionsupporting
confidence: 84%
“…This is a minimum estimate because some women in this situation would not have obtained treatment. This rate is much higher than that found when the procedure is performed by trained personnel in hygienic settings,* [4][5][6] and is an indicator of the extent to which unsafe MR is taking place.…”
Section: Morbidity Related To Abortion and Mr Proceduresmentioning
confidence: 72%
“…The ratio of induced abortions to live births was 18 per 100 nationally; Khulna and Rajshahi had the highest abortion ratios (34 and 25, respectively), while Barisal, Chittagong and Sylhet had the lowest (6)(7)(8)(9)(10)(11)(12)(13)(14). This measure is an indicator of the likelihood that, once pregnant, a woman will have an induced abortion: The national ratio of 18 per 100 births means that approximately one woman has an induced abortion for every five who give birth.…”
Section: Change In Morbidity Mrs and Induced Abortionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis examined the complication rates of EVA versus MVA for firsttrimester procedural abortion and concluded that MVA may be marginally safer. 25 In addition, complication rates are increased by including patients with pregnancies at 12 to 14 weeks gestation. For example, all 12 cases of postabortion vaginal bleeding requiring hospitalization occurred in this gestational age range.…”
Section: Complicationsmentioning
confidence: 99%